Une leçon de domestication par Vincent et Boyer-Fonfrède (1795-1797) : pédagogie et zooagogie au cœur du projet républicain du Directoire - Malik Mellah (Cahiers d’histoire.)
The aim of the article is to read Vincent’s famous painting La Leçon de labourage as an opportunistic or sincere way for the manufacturer Boyer-Fonfrède to seize upon the « Thermidorian » promotion of human and agricultural sciences in order to contribute to the construction of a new social and political order. It is also a question of making it the starting point of a reflection on the mobilization of the figures of domestication and on what can be a directorial republican ecology.